Prefixal Innovations as a Mean of Psychological Impact on Consciousness Ofrecipient - Nataliia Kostusiak; Oleksandr Mezhov (Психолінгвістика)
The article characterizes structural and derivation features of innovations, which have enriched language system during the beg inning of the XXI century and are presented in Ukrainian media text. It is emphasized on the importance of interaction between external factors and language dynamic, the advantage of studying of prefixal innovations, taking into account the text environment, functional-stylistic, and psycholinguistic specifications was grounded. It was mentioned, that most of the innovations have negative emotional-expressive evaluation. They include derivatives with prefixal morphemes псевдо-, квазі-, лже-, it was indicated the part-language accessory of these lexemes, their thematic grouping was proposed. It was found out the using conditions and manipulating potential of language units with prefix недо-. It was also analyzed emotional-expressive coloration and pragmatic direction of innovations with formant пост-. Used in the press, prefixal morphemes анти-, гіпер- are consider edas components with double function, since they can mark both negative and positive features due to the con text. Functional-psycholinguistic analysis has caused the differentiation of small group of lexemes with prefixes де-, контр-, which also have evaluating connotations, however un like mention edabove un its, are greatly specialized on explication of positive emotional-evaluating influence on the recipient. Different writing of analyzed innovations has caused the abusing of problem of their standardized forming.  In that case a specific dichotomy appears: from one side used in publicism words of mentioned sample shall comply with current norms of “Ukrainian orthography”, and from another – lexemes, formed with some orthographic faults, partly exacerbate the psychological impact on the recipient.